Abrasion Induced Volume Loss in Porcine Teeth Measured Using X-Ray Microtomography - Kao, Alexander P.; Khan, Shaz; Barber, Asa H. (Frontiers in Mechanical Engineering, 2018)
Teeth are complex biological structures consisting primarily of enamel and dentin. The mechanical loading of teeth due to the action of brushing provides a complex interaction between applied forces and the biological structure, resulting in volume loss of dental tissue. The volume loss as a resulting of using an ex situ brushing of teeth was measured using x-ray microcomputed tomography (XCT) and corresponding image analyses. 3-dimension reconstructions of teeth reveal a considerably loss of dentin at a rate of over thirty times that of enamel during brushing, as would be expected by the consideration of the corresponding structures. The approach here is flexible and can be applied to a range of brushing, teeth and environmental conditions.